Peptide Receptor Radionuclide Therapy Using 177Lu-DOTATATE in Advanced Neuroendocrine Tumors (NETs) in a Limited-Resource Environment - Kalantarhormozi, Mohammadreza; Hassanzadeh, Samaneh; Rekabpour, Seyed Javad; Ravanbod, Mohammad Reza; Jafari, Esmail; Amini, AbdulLatif; Dadgar, Habibollah; Mahmoudpour, Mehdi; Nabipour, Iraj; Jokar, Narges; Assadi, Majid (World Journal of Nuclear Medicine, 2022)
Background This study was conducted to evaluate the clinical efficacy and safety of peptide receptor radionuclide therapy (PRRT) using 177Lu-DOTA0-Tyr3-octreotate (DOTATATE) in patients with neuroendocrine tumors (NETs).Methods Sixteen patients with pathologically verified NETs including eight females and eight males were enrolled in this study. Before PRRT, the patients underwent 68Ga-DOTATATE positron emission tomography/computed tomography or 99mTc-octreotide scintigraphy for evaluation of somatostatin receptor expression. Response to treatment was assessed according to the Response Evaluation Criteria In Solid Tumors (RECIST) classified as complete response (CR), partial response (PR), stable disease (SD), and progressive disease (PD). In addition, for evaluation of toxicity, monthly blood analysis was performed including hematology, renal function (creatinine) test, and liver function test. The Eastern Cooperative Oncology Group (ECOG) status performance was applied to estimate the patients' general condition in a scale of 0 (fully active) to 5 (dead). In addition, overall survival (OS) was calculated as the time interval from the start of PRRT to death from any reason.Results Sixteen patients including eight females and eight males with a median age of 60.5 years (range: 24–74) were enrolled in this study. The patients underwent PRRT with a median cycle of 3.5 (range: 1–7) and a median dose of 20.35 (range: 7.4–49.95 GBq). At the end of data collection, PR, CR, SD, and PD were seen in 11, 2, 1, and 2 patients according to the RECIST, respectively. Three patients expired during or after the PRRT period. The median ECOG and Karnofsky Performance Scale was 1.5 and 75 before PRRT, which improved significantly to 1 and 80 after PRRT, respectively (p < 0.05). According to the Kaplan–Meier test, the median OS was 23 months (95% confidence interval: 7.90–38.09). According to the National Cancer Institute's Common Terminology Criteria for Adverse Events, three patients showed grade I and three patients showed grade II leucopenia. Furthermore, three and seven patients had grade II and grade I anemia, respectively.Conclusion Since PRRT using 177Lu-DOTATATE has a favorable response rate and few adverse effects and improves the quality of life in NETs, it can be used as an effective therapeutic option, especially in nonoperative, metastatic, and progressive NETs.
Keywords: neuroendocrine tumors (NETs); peptide receptor radionuclide therapy (PRRT); 177Lu-DOTATATE; 68Ga-DOTATATE PET-CT; 99mTc-octreotide scintigraphy